Information Systems and Public Sector Accountability - RICHARD HEEKS (Working Paper Series Paper No. 1, 1998)
Increased accountability is a key component of public sector reform. This paper investigates the relationship between accountability and both information technology and information systems. It concludes that IT has had a very mixed impact, supporting accountability in some cases, but also skewing or undermining it in others. Information systems - computerised or not - are an essential part of public sector accountability. However, new IS have a flexible impact, with accountability outcomes being determined mainly by management decisions and by wider organisational and environmental factors. As such, the broader context must be conducive to accountability before accountability IS initiatives will work.